Transformation of vernacular housing pattern in periurban Abuja-Nigeria due to informal urbanism, 1976-2006 - Mai, Moukhtar M. (2007)
The phenomenon of informal housing is common to most cities of developing courtiers. Its role as single housing delivery mechanism has seriously challenged the popular notion held by policy makers, planners and architects. Informality is today a paradigm of city making in Africa, Asia and Latin America. The concurrence of informal housing with informal urbanism and housing poverty demands the concerted attention architects, planners, sociologist, urban designers and economists to articulate an appropriate paradigm that could effectively cart the way forward to housing for all year 2010. The research employs a three tier qualitative evaluation strategies to describe the characters of the case study, identify its trend of transformation, and determine the propelling motives for the virtual lost of its vernacular identity. This integrated approach is triangulated with photo recognition, purposively sampled compound plans, as well as a quantitative survey of the phenomenon. The preliminary findings of this study indicate that, for the indigenous Gbagyi community in Abuja urban fringes, their natural habitat seems to be threatened. The sustainability of its vernacular housing pattern physically, socially and psychologically may not survive the current urbanization trend. This could culminate in the lost of the spatial identity. For one, these settlements are expanding exponentially. For another, Gbagyi spatial identity of communal habitation of multiple courtyard compounds, dotted with symbolic tombs and granaries punctuating habitable spaces, sitting on ancestral plots, where the spirit of the dead inspires the living; the young and the old are psychologically glued to the living dead ‘the ancestral spirits,’ whose views are thought on survival issues, as and when required, is becoming extinct. The processes of housing identity were a times an intentional, but they still impact the settlement’s physical landscape. For instance the vernacular Gbagyi rural housing norms in the study area could not be transformed into ‘its own’ urban norms due to economic superiority of income over cultural sustainability. This is attributable to social mobility and its attendant economic and socio-cultural consequences. Although this case study is local, it is a pointer to global trends of housing delivery and identity.